Genetic Evidence for Early Peritoneal Spreading in Pelvic High-Grade Serous Cancer - Chien, Jeremy; Neums, Lisa; Powell, Alexis F. L. A.; Torres, Michelle; Kalli, Kimberly R.; Multinu, Francesco; Shridhar, Viji; Mariani, Andrea (Frontiers in Oncology, 2018)
Background Most pelvic high-grade serous (HGS) carcinomas have been proposed to arise from tubal primaries that progress rapidly to advanced disease. However, the temporal sequence of ovarian and peritoneal metastases is not well characterized. Methods To establish the sequence of metastases, phylogenetic relationships among the ovarian and peritoneal carcinomas were determined from single-nucleotide variations (SNVs) in nine tumor regions from each patient with pelvic HGS carcinomas. Somatic SNVs from each tumor sample were used to reconstruct phylogenies of samples from each patient. Variant allele frequencies were used to reconstruct subclone phylogenies in each tumor sample. Results We show that pelvic HGS carcinomas are highly heterogeneous, only sharing less than 4% of somatic SNVs among all nine carcinoma implants in one patient. TP53 mutations are found in all nine carcinoma implants in each patient. The phylogenetic analyses reveal that peritoneal metastases arose from early branching events that preceded branching events for ovarian carcinomas in some patients. Finally, subclone phylogenies indicate the presence of multiple subclones at each tumor implant and early tumor clones in peritoneal implants. Conclusion The genetic evidence that peritoneal implants arose before or concurrently with ovarian implants is consistent with the emerging concept of the extra-ovarian origin of pelvic HGS cancer. Our results challenge the concept of stepwise spatial progression from the fallopian primary to ovarian carcinomas to peritoneal dissemination and suggest an alternative progression model where peritoneal spreading of early clones occurs before or in parallel with ovarian metastases.